2018
DOI: 10.4274/balkanmedj.2017.1471
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Adeno-Neuroendocrine Carcinoma; Case Series of Ten Patients with Review of the Literature

Abstract: Aims:Mixed adeno-neuroendocrine carcinoma is a rare entity, diagnosed with immunohistochemical studies. Literature mainly includes case reports and series which are very few. In our study, we aimed to report a case series from a tertiary hospital with demographics of the patients, detailed tumor and clinical findings and follow-up plus survival conditions.Methods:Pathology database was explored for patients with the pathological diagnosis of ‘mixed adeno-neuroendocrine carcinoma’ and patients were identified r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 17 publications
(35 reference statements)
0
25
0
Order By: Relevance
“…In that setting, outcomes of preoperative biopsies of these lesions may be misleading as the neuroendocrine component is not easily or adequately recognized. Notably, it has also been observed that the neuroendocrine cancer (NEC) component may display higher proliferative activity than the adenocarcinomatous component, possibly implying that the neuroendocrine part (NEC) in biliary MANEC could dictate long-term outcomes in these patients (11,29). As far as the immunohistochemical profile of these tumors is concerned, a minimum of two out of three regularly used markers, namely SynA, CgA and Cluster of Differentiation 56 (CD56), ought to be diffusely expressed to confirm the diagnosis of high-grade MANEC (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that setting, outcomes of preoperative biopsies of these lesions may be misleading as the neuroendocrine component is not easily or adequately recognized. Notably, it has also been observed that the neuroendocrine cancer (NEC) component may display higher proliferative activity than the adenocarcinomatous component, possibly implying that the neuroendocrine part (NEC) in biliary MANEC could dictate long-term outcomes in these patients (11,29). As far as the immunohistochemical profile of these tumors is concerned, a minimum of two out of three regularly used markers, namely SynA, CgA and Cluster of Differentiation 56 (CD56), ought to be diffusely expressed to confirm the diagnosis of high-grade MANEC (30).…”
Section: Discussionmentioning
confidence: 99%
“…MANECs most commonly arise in the colon, appendix, rectum or stomach (8)(9)(10)(11), however a limited number of MANECs have been reported to originate from the bile duct, the pancreas and the gallbladder (12)(13)(14).…”
mentioning
confidence: 99%
“…The common sites for MANEC are colon and stomach, but cases have been reported from the esophagus, rectum, pancreas, biliary tract and uterine cervix. 4 There is no clear gender predilection for MANEC. [4][5][6][7] Most cases are locally aggressive during the time of diagnosis (≥ pT3) however both our cases were at stage pT.…”
Section: Discussionmentioning
confidence: 99%
“…4 There is no clear gender predilection for MANEC. [4][5][6][7] Most cases are locally aggressive during the time of diagnosis (≥ pT3) however both our cases were at stage pT. 2,5,7 Colonoscopy is a relatively reliable modality for diagnosing colorectal carcinoma, however, the gross morphology of MANEC is similar to adenocarcinoma hence histopathological examination is crucial for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…These tumors did not exhibit specific symptoms nor did specific radiological or laboratory tests of them reveal unique findings; hence, a diagnosis depends on postoperative histopathological and immunohistochemical studies. There is also conflicting evidence regarding the prognosis of patients with MANEC [10].…”
Section: Introductionmentioning
confidence: 99%